Vascular Neurosurgery : In Multiple-Choice Questions - Hoz, Samer S. (Springer International Publishing : Imprint: Springer, 2017)
This book is a guide dedicated to vascular pathologies affecting the central nervous system. It uses a multiple-choice format with more than 340 genuine MCQs in a convenient format that is ideal for self-study. Seven chapters provide comprehensive coverage of core concepts in vascular neurosurgery. The questions are structured and organized so as to offer a step-by-step description of each disease, from the definition, related anatomy, pathology, clinical features, radiology to surgical decisions and operative tricks. Answers and explanations appear directly below the questions to make reading easy. This book is essential for residents across neurosurgical disciplines as it includes most of the neurovascular information neurosurgical residents need to prepare for their certification exam. It is also beneficial for those seeking a refresher or for those preparing for certification maintenance. .
Keywords: Medicine.; Neurology.; Neurosurgery.; elektronické knihy; electronic books